Reflections about a single checksum - (:unkn) unknown (My University, 2010)
A single checksum for codes consisting of n integer components is investigated. In coding theory this is mostly used for single error-correction in unconventional error models. If the errors are such that a single component ci is distorted to ci±ei, the analysis leads to equivalent group factorizations. We shall present several code constructions for this model, give a short survey on the coding theoretical and mathematical background, and also emphasize applications in cryptography and computer science. © 2010 Springer-Verlag Berlin Heidelberg.
Keywords: Distributed computing; Group factorization; Perfect codes; Single - error correction; Steganography